SOA Generic Views - In the Eye of the Beholder - Eicker, Stefan; Jung, Reinhard; Schwittek, Widura; Spies, Thorsten (Proceedings of the 2008 IEEE International Conference on Services Computing (SCC 2008), IEEE Congress on Services 2008, WebX 2008 Workshop, 2008)
This paper presents an approach called Generic View Concept which facilitates the creation and visualization of role-based, task-oriented views on service-oriented architectures. Those views enhance the understanding from the technical and functional point of view, and thus reduce the inherent complexity arising during the creation, use and maintenance of service-oriented architectures. The unique aspect of the Generic View Concept is that it does not constrain stakeholders to a set of predefined views. In order to examine the usefulness of Generic Views in real world scenarios, a prototype has been implemented applying 3D visualization techniques.
Keywords: SOA; Generic Views; Architecture; Views; Visualization; Complexity; SOA governance